An electrode sheet, a method of manufacturing the same, a battery, and an electric device
Patent Information
- Application Number
- CN202510500335.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-18
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]本发明提供一种电极片,能够降低电解液在电极片中的液相扩散阻抗并解决电极片内部电流密度不匀导致的内阻增大问题
[0054]本发明实施例提供的电极片,通过在电极集流体的不同区域设置不同的区域并填充不同粒径大小的活性材料,能够降低电极片的液相扩散阻抗并解决电极片内部电流密度不匀导致的内阻增大问题,有利于降低电池的内阻并提升电池的循环寿命。
Smart Images

Figure CN122968237A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and in particular to an electrode sheet and its preparation method, a battery, and an electrical device. Background Technology
[0002] With the booming development of the new energy vehicle industry in recent years, consumers have put forward increasingly higher requirements for battery energy density and fast charging performance.
[0003] During the battery manufacturing process, uneven current intensity is a common problem in electrode sheets. This is mainly due to the resistance of the electrode current collector itself. During rapid charging and discharging, the current density is higher in the area near the tab, while the current density is lower in the area far from the tab due to excessive resistance. Active metal ions may deposit as elemental metals on the electrode surface with higher current density. In addition to reducing the energy density and capacity of the battery, this also leads to an increase in battery resistance and reduces the cycle life of the battery.
[0004] Therefore, there is an urgent need for an electrode sheet that can improve the problem of increased internal resistance caused by uneven current density inside the electrode sheet, thereby improving the cycle life of the battery. Summary of the Invention
[0005] This invention provides an electrode sheet that can reduce the liquid phase diffusion impedance of the electrolyte in the electrode sheet and solve the problem of increased internal resistance caused by uneven current density inside the electrode sheet.
[0006] The present invention provides a method for preparing an electrode sheet, which is used to prepare the above-mentioned electrode sheet. The prepared electrode sheet has a low liquid phase diffusion resistance and can balance the internal current density.
[0007] The present invention provides a battery comprising the above-described electrode sheet, wherein the battery has low internal resistance and long cycle life.
[0008] This invention provides an electrical device that has high safety and reliable operation over a long period of time.
[0009] This invention provides an electrode sheet, comprising:
[0010] Electrode current collector;
[0011] Active layer;
[0012] The active layer includes a first active layer located on at least one side of the electrode current collector, the first active layer including a first active material, the first active material including a first sub-active material and a second sub-active material;
[0013] The first active layer includes a first region and a second region located on at least one side of the first region, wherein the second region is located between the first region and the outer edge of the electrode sheet;
[0014] The n value of the first region is less than the n value of the second region;
[0015] The value of n is the ratio of the particle size of the second sub-active material to the particle size of the first sub-active material, and the value of n is ≥1.
[0016] In some embodiments of the present invention, the value of n in the first region is 1 to 1.1;
[0017] And / or, the particle size of the first sub-active material in the first region is smaller than the particle size of the first sub-active material in the second region;
[0018] And / or, the particle size of the first sub-active material in the first region is 5 to 15 μm, preferably 10 to 12 μm;
[0019] And / or, the particle size of the second sub-active material in the first region is 5 to 17 μm, preferably 10 to 14 μm.
[0020] In some embodiments of the present invention, the second region includes at least two sub-regions distributed along a first direction, the first direction being parallel to the direction from the first region to the second region; in every two adjacent sub-regions, the n value of the sub-region closer to the first region is less than the n value of the sub-region farther from the first region.
[0021] In some embodiments of the present invention, the ratio a of the n value of the sub-region closest to the first region to the n value of the first region is 1 < a < 1.35, and preferably a of 1.12 ≤ a ≤ 1.31.
[0022] And / or, the n value of the sub-region closest to the first region is 1 < n < 1.35, preferably the n value of the sub-region closest to the first region is 1.12 ≤ n ≤ 1.31;
[0023] And / or, the n value of the sub-region next to the first region is 1.35≤n≤4, preferably the n value of the sub-region next to the first region is 1.8≤n≤2.2;
[0024] And / or, in any two adjacent sub-regions, the ratio b of the n value of the sub-region farther from the first region to the n value of the sub-region closer to the first region is 1 < b < 4, preferably b of 1.36 ≤ b ≤ 2;
[0025] And / or, the particle size of the first sub-active material in the first region is smaller than the particle size of the first sub-active material in the sub-region closest to the first region, preferably the ratio of the particle size of the first sub-active material in the sub-region closest to the first region to the particle size of the first sub-active material in the first region is (1~1.5):1; preferably the ratio of the particle size of the first sub-active material in the sub-region closest to the first region to the particle size of the first sub-active material in the first region is (1.1~1.2):1;
[0026] And / or, the particle size of the first sub-active material in the sub-region closest to the first region is 8 to 30 μm;
[0027] And / or, the particle size of the first sub-active material in the sub-region closest to the first region is 12 to 40 μm;
[0028] And / or, in any two adjacent sub-regions, the particle size of the first sub-active material in the sub-region closer to the first region is smaller than the particle size of the first sub-active material in the sub-region farther from the first region. Preferably, the ratio of the particle size of the first sub-active material in the sub-region farther from the first region to the particle size of the first sub-active material in the sub-region closer to the first region is (1.15 to 5):1; preferably, the ratio of the particle size of the first sub-active material in the sub-region farther from the first region to the particle size of the first sub-active material in the sub-region closer to the first region is (1.2 to 1.8).
[0029] And / or, in any two adjacent sub-regions, the length of the sub-region closer to the first region in the first direction is less than the length of the sub-region farther from the first region in the first direction, preferably the ratio of the length of the sub-region closer to the first region in the first direction to the length of the sub-region farther from the first region in the first direction is (0.6~1):1;
[0030] And / or, the ratio d of the length of any of the sub-regions in the first direction to the length of the first active layer in the first direction is 0.05 ≤ d < 1, preferably 0.35 ≤ d ≤ 0.6;
[0031] And / or, the length of any of the sub-regions in the first direction is 50 to 990 cm, preferably 50 to 80 cm.
[0032] Some embodiments of the present invention further include a second active layer located on the side of the first active layer opposite to the electrode current collector.
[0033] In some embodiments of the present invention, the second active layer includes a second active material, wherein the particle size of the second active material is greater than or equal to the particle size of the first sub-active material in the first region;
[0034] Preferably, the particle size ratio of the second active material to the particle size of the first sub-active material in the first region is (1.25~3):1;
[0035] Preferably, the particle size of the second active material is 15–30 μm.
[0036] In some embodiments of the present invention, the thickness of the second active layer is less than the thickness of the first active layer;
[0037] Preferably, the ratio g of the thickness of the second active layer to the thickness of the first active layer is 0.2 ≤ g < 1;
[0038] Preferably, the thickness of the second active layer is 15–30 μm;
[0039] Preferably, the thickness of the first active layer is 40–80 μm.
[0040] In some embodiments of the present invention, the compaction density of the active layer is 1.1–2 g / cm³. 2 ;
[0041] And / or, the areal density of the active layer is 230–700 g / m³. 2 .
[0042] In some embodiments of the present invention, the length of the first region in the first direction is a proportion i of the length of the first active layer in the first direction, where i is 0.01 ≤ i < 1;
[0043] And / or, the length of the first region in the first direction is 1 to 950 cm;
[0044] Wherein, the first direction is parallel to the direction along the first region to the second region.
[0045] In some embodiments of the present invention, the second region exists on both opposite sides of the first region;
[0046] And / or, the first region and the second region are distributed along the length of the electrode sheet.
[0047] In some embodiments of the present invention, the electrode sheet further includes a tab connected to the electrode current collector, and the second region is located between the first region and the tab.
[0048] In some embodiments of the present invention, the electrode sheet is a negative electrode sheet or a positive electrode sheet.
[0049] This invention also provides a method for preparing the electrode sheet as described above, comprising the following steps:
[0050] The first electrode paste is coated on at least one side of the electrode current collector to form the first active layer, thereby obtaining the electrode sheet;
[0051] The first electrode paste includes a first paste for forming the first region and a second paste for forming the second region. The first paste is applied to the electrode current collector at a position corresponding to the first region to form the first region of the first active layer, and the second paste is applied to the electrode current collector at a position corresponding to the second region to form the second region of the first active layer.
[0052] This invention also provides a battery, including the electrode sheet as described above or the electrode sheet prepared according to the electrode sheet preparation method described above.
[0053] This invention also provides an electrical device, including the battery described above.
[0054] The electrode sheet provided in this embodiment of the invention, by setting different regions in different areas of the electrode current collector and filling them with active materials of different particle sizes, can reduce the liquid phase diffusion resistance of the electrode sheet and solve the problem of increased internal resistance caused by uneven current density inside the electrode sheet, which is beneficial to reduce the internal resistance of the battery and improve the cycle life of the battery. Attached Figure Description
[0055] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0056] Figure 1 This is a schematic diagram of the first active layer provided in an embodiment of the present invention;
[0057] Figure 2 A schematic diagram of the first active layer provided in another embodiment of the present invention;
[0058] Figure 3 This is a schematic diagram of a battery provided according to an embodiment of the present invention.
[0059] Explanation of reference numerals in the attached figures:
[0060] 1: Electrode current collector;
[0061] 2: First active layer;
[0062] 21: First area;
[0063] 22: Second area;
[0064] 221: The sub-region closest to the first region;
[0065] 222: The sub-region closest to the first region;
[0066] 3: Positive electrode plate;
[0067] 4: Negative electrode plate;
[0068] 5: Diaphragm.
[0069] The accompanying drawings illustrate specific embodiments of the invention, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the invention in any way, but rather to illustrate the concept of the invention to those skilled in the art through reference to particular embodiments. Detailed Implementation
[0070] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0071] Currently, during the battery manufacturing process, uneven current density on the electrode sheets can lead to the precipitation of active metal ions during long-term cycling, resulting in problems such as cycle dropout, increased internal resistance, and low cycle life, which urgently need to be addressed.
[0072] Through long-term research, the inventors of this application have discovered that during the charging and discharging test of batteries, the electrode sheets generally suffer from uneven current density. The reason for this is that, due to factors such as the structure and manufacturing process of the electrode sheets, the impedance of different regions of the electrode sheets is usually different, which leads to uneven current density of the electrode sheets during the charging and discharging process of the battery. Specifically, the impedance of the central region of the electrode sheet along its length is usually higher than that of the edge region, which makes the current density of the central region of the electrode sheet lower than that of the edge region, resulting in uneven current density of the electrode sheets during the charging and discharging process of the battery.
[0073] Uneven current density on the electrode sheets can easily lead to surface lithium plating (taking lithium batteries as an example) and subsequent cycle life drops during long-term battery cycling, affecting the battery's cycle life. Therefore, improving current density uniformity through reasonable electrode sheet structure design, thereby improving battery cycle life and other performance characteristics, is a significant challenge.
[0074] Based on this, such as Figure 1 As shown, an embodiment of the present invention provides an electrode sheet, including an electrode current collector 1; an active layer; the active layer includes a first active layer 2 located on at least one side of the electrode current collector, the first active layer 2 including a first active material, the first active material including a first sub-active material and a second sub-active material; the first active layer includes a first region 21 and a second region 22 located on at least one side of the first region 21, and the second region 22 is located between the first region 21 and the outer edge of the electrode sheet; the n value of the first region 21 is less than the n value of the second region 22; the n value is the ratio of the particle size of the second sub-active material to the particle size of the first sub-active material, and the n value is ≥1.
[0075] The electrode sheet of this invention can balance the current density inside the electrode sheet, thereby improving the cycle life of the battery.
[0076] In this embodiment, the particle size is the average particle size.
[0077] In detail, the second region is located between the first region and the outer edge of the electrode sheet, that is, the projection of the second region on the electrode current collector is located between the projection of the first region on the electrode current collector and the outer edge of the electrode current collector.
[0078] In some embodiments, the n value of the first region 21 is less than the n value of the second region 22; the n value is the ratio of the particle size of the second sub-active material to the particle size of the first sub-active material, that is, the particle size of the second sub-active material is greater than or equal to the particle size of the first sub-active material (i.e., n value ≥ 1). The particle size of the first sub-active material is the average particle size (D50), and the particle size of the second sub-active material is also the average particle size (D50).
[0079] In detail, n is the ratio of the particle size of the second sub-active material to the particle size of the first sub-active material. That is, if the second active material and the first sub-active material are located in the first region, the n value is the n value of the first region; if the second active material and the first sub-active material are located in the second region, the n value is the n value of the second region.
[0080] When n equals 1, the particle size of the first sub-active material is the same as that of the second sub-active material, meaning that there is only one type of active material in this region.
[0081] In practice, the battery can be disassembled to separate the electrode sheets. Then, an SEM is used to photograph the cross-sections of the first and second regions of the electrode sheets. The particle size of each first active material particle in the SEM image is measured. During measurement, the particle sizes of the first active material particles within the field of view are sorted in descending order. The average particle size of the top 40 first active material particles is selected as the average particle size of the second sub-active material, and the average particle size of the bottom 40 first active material particles is selected as the average particle size of the first sub-active material. The n value is then calculated based on this. Alternatively, the average particle size of the top 50 first active material particles can be selected as the average particle size of the second sub-active material, and the average particle size of the bottom 50 first active material particles can be selected as the average particle size of the first sub-active material. The n value is then calculated based on this.
[0082] The present invention does not impose any special limitations on the selection of the first active material, and it can be selected according to the actual situation.
[0083] According to the inventor's research and analysis, the electrode sheet of the present invention can balance the current density within the electrode sheet. This is because the present invention divides the electrode sheet into sections (a first region and a second region located on at least one side of the first region). The second region, which has a higher current density near the edge (and also near the tab), is filled with a first active material with a larger n value (i.e., the particle size difference between the first and second active materials is large). This results in a more disordered and tortuous internal structure of the first active material in the second region. In other words, a larger n value leads to increased tortuosity in the second region. Increased tortuosity leads to a corresponding increase in liquid phase diffusion resistance, affecting the mass transfer efficiency within the electrode sheet. That is, when active metal ions and electrons in the current pass through this region, they need to traverse a more complex and longer path. Furthermore, increased tortuosity restricts the free movement space of active metal ions and electrons in this region. Therefore, it slows down the process of active metal ions in the second region being reduced to elemental metals, without increasing the internal resistance of the battery, thus improving the cycle life of the battery. Meanwhile, the current density is lower in the first region far from the electrode tab. In this embodiment of the invention, the first active material with a smaller n value (i.e., the particle size difference between the first sub-active material and the second sub-active material is large) is filled in the first region. Therefore, the arrangement of the first active material in the first region is simpler and more orderly. The liquid phase diffusion impedance in this region is less than that in the second region. As a result, the active metal ions and electrons in the battery can shuttle more quickly in the first region, reducing the problem of low utilization rate of active material caused by low current density in the center region (first region) of the electrode sheet, and also helping to improve the cycle life of the battery.
[0084] In detail, the mass transfer capacity within the electrode sheet can be measured by its tortuosity, which is calculated as follows:
[0085]
[0086] Where K0 refers to the electrolyte conductivity, expressed in μS / m; ε refers to the theoretical porosity (measured using mercury porosimetry), expressed in %; and S is the electrode pad coating area (active layer area), expressed in m². 2 Calculate; R i d0 is the liquid-phase diffusion resistance of ions (active metal ions) per unit area within the electrode sheet (measured using an electrochemical workstation); d0 is the electrode sheet thickness, in meters.
[0087] In some embodiments of the present invention, when the tortuosity of the first region is 2 to 4, the cycle life of the battery is higher. Preferably, the tortuosity of the first region is 3.5 to 3.7.
[0088] In some embodiments, the battery has a higher cycle life when the tortuosity of the sub-region closest to the first region is 2 to 3.9. Preferably, the tortuosity of the sub-region closest to the first region is 3.4 to 3.7.
[0089] In some embodiments, the battery cycle life is higher when the tortuosity of the sub-region closest to the first region is 2 to 3.8. Preferably, the tortuosity of the sub-region closest to the first region is 3.2 to 3.7.
[0090] In some embodiments of the present invention, when the porosity of the electrode sheet is 25% to 35%, the mass transfer capacity inside the electrode sheet is stronger, which is more conducive to improving the cycle life of the battery.
[0091] In some embodiments of the present invention, the electrode dressing area S is 0.004662 m². 2 The electrolyte conductivity is 0.883 μS / m, and the electrode thickness d0 is 0.000144 m.
[0092] In some embodiments, the value of n in the first region is 1 to 1.1. In this case, the active metal ions in the battery have a easier diffusion path in the first region with a lower current density, which can make more effective use of the first active material in the region, thereby improving the cycle life of the battery.
[0093] In some embodiments, the particle size of the first sub-active material in the first region is smaller than that of the first sub-active material in the second region. The particle size is also the average particle size. By providing a first sub-active material with a larger average particle size in the second region, the tortuosity in the second region can be further improved, thereby better improving the problem of active metal ion precipitation, which is conducive to better reducing the internal resistance of the battery and improving the cycle life of the battery.
[0094] In some embodiments, when the particle size of the first sub-active material in the first region is 5–15 μm, the tortuosity in the first region can be further reduced, thus improving the cycle life of the battery. Preferably, the particle size of the first sub-active material in the first region is 10–12 μm.
[0095] In some embodiments, when the particle size of the second sub-active material in the first region is 5–17 μm, the tortuosity in the first region can be further reduced, thus improving the cycle life of the battery. Preferably, the particle size of the first sub-active material in the first region is 10–14 μm.
[0096] In some embodiments of the present invention, such as Figure 2 As shown, the second region includes at least two sub-regions 221 (the sub-region closest to the first region) and 222 (the sub-region next closest to the first region) distributed along a first direction, the first direction being parallel to the direction from the first region to the second region; in every two adjacent sub-regions, the n-value of the sub-region closer to the first region is less than the n-value of the sub-region farther from the first region. By configuring the second region of the electrode current collector as described above, this embodiment of the invention facilitates better subdivision of regions with different current density distributions within the second region, thereby further improving the problem of active metal ion deposition within the second region. Specifically, the second region is the second region on either side of the first region of the electrode sheet, and for the second region on either side of the first region, the second region includes at least two sub-regions distributed along the first direction.
[0097] In some embodiments of the present invention, the ratio a of the n value of the sub-region closest to the first region to the n value of the first region is 1 < a < 1.35. When the electrode sheet meets the above requirements, it is beneficial to better balance the current density in the electrode sheet, better reduce the internal resistance of the battery, and further improve the cycle efficiency of the battery. Preferably, the ratio a of the n value of the sub-region closest to the first region to the n value of the first region is 1.12 ≤ a ≤ 1.31.
[0098] In some embodiments, when the n value of the sub-region closest to the first region is 1 < n < 1.35, the current density in the electrode sheet is more uniform. Preferably, the n value of the sub-region closest to the first region is 1.12 ≤ n ≤ 1.31.
[0099] In some embodiments, when the value of n for the sub-region closest to the first region is 1.35 ≤ n ≤ 4, the current density inside the electrode sheet can be better balanced. Preferably, the value of n for the sub-region closest to the first region is 1.8 ≤ n ≤ 2.2.
[0100] In some embodiments, in any two adjacent sub-regions, the ratio b of the n value of the sub-region farther from the first region to the n value of the sub-region closer to the first region is 1 ≤ b ≤ 4, which further reduces the internal resistance of the battery, thus improving the cycle life of the battery. Preferably, the ratio b of the n value of the sub-region farther from the first region to the n value of the sub-region closer to the first region is 1.36 ≤ b ≤ 2.
[0101] In some embodiments, the particle size of the first sub-active material in the first region is smaller than the particle size of the first sub-active material in the sub-region closest to the first region. Preferably, the ratio of the particle size of the first sub-active material in the sub-region far from the first region to the particle size of the first sub-active material in the sub-region close to the first region is (1 to 1.5):1; preferably, the ratio of the particle size of the first sub-active material in the sub-region closest to the first region to the particle size of the first sub-active material in the first region is (1.1 to 1.2):1.
[0102] In detail, the particle size of the first active material mentioned above is the average particle size, and the specific testing method is as described above. At this time, the electrode sheet has a more reasonable structure, which further balances the current density in different regions inside the electrode sheet, which is beneficial to further reduce the internal resistance of the battery and thus better improve the cycle life of the battery.
[0103] In some embodiments, the particle size of the first sub-active material in the sub-region closest to the first region is 8–30 μm. For example, the particle size of the first sub-active material in the sub-region of the first region is, for example, a range of 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 28 μm, 30 μm, or any combination thereof. When the particle size of the first sub-active material in the sub-region closest to the first region is within the above range, it is beneficial to better balance the current density within the electrode sheet and further improve the deposition of active metal ions in the battery.
[0104] In some embodiments, the particle size of the first sub-active material in the sub-region closest to the first region is 12–40 μm, and the particle size of the first sub-active material in the sub-region closest to the first region is, for example, a range of 12 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, or any combination thereof. By further controlling the particle size of the first sub-active material in the sub-region closest to the first region, embodiments of the present invention facilitate further equalization of the current density within the electrode sheet, thereby improving the cycle life and other performance characteristics of the battery.
[0105] In some embodiments, in any two adjacent sub-regions, the particle size of the first sub-active material in the sub-region closer to the first region is smaller than that in the sub-region farther from the first region. Preferably, the ratio of the particle size of the first sub-active material in the sub-region closer to the first region to that in the sub-region farther from the first region is (1.15-5):1:1; more preferably, the ratio is (1.2-1.8). By controlling the particle size relationship between the first sub-active material in the sub-region closer to the first region and the first sub-active material in the sub-region farther from the first region, the embodiments of the present invention can further reduce the impact of uneven current intensity inside the electrode sheet on the internal resistance of the battery, thereby improving the battery's cycle life and other performance characteristics.
[0106] In some embodiments of the present invention, the particle size of the second active material is larger than the particle size of the first sub-active material in the sub-region next closest to the first region, the particle size of the first sub-active material in the sub-region next closest to the first region is larger than the particle size of the first sub-active material in the sub-region closest to the first region, and the particle size of the first sub-active material in the sub-region closest to the first region is larger than the particle size of the first sub-active material in the first region.
[0107] In some embodiments, in any two adjacent sub-regions, the length of the sub-region closer to the first region in the first direction is less than the length of the sub-region farther from the first region in the first direction. Preferably, the ratio of the length of the sub-region closer to the first region in the first direction to the length of the sub-region farther from the first region in the first direction is (0.6~1):1. When the electrode sheet in the embodiments of the present invention has the above structure, the problem of increased battery internal resistance caused by uneven current density is further improved, which is beneficial to improving the battery's cycle life and other performance characteristics.
[0108] In some embodiments, the ratio d of the length of any sub-region in the first direction to the length of the first active layer in the first direction is 0.05 ≤ d < 1. When the ratio of the length of any sub-region in the first direction to the length of the first active layer in the first direction is within the above range, the problem of uneven current density inside the electrode sheet can be further improved, which is beneficial to improving the cycle life and other performance of the battery. For example, the ratio d of the length of the sub-region closest to the first region in the first direction to the length of the first active layer in the first direction can be 0.05 ≤ d < 1, and the ratio d of the length of the sub-region next closest to the first region in the first direction to the length of the first active layer in the first direction can be 0.05 ≤ d < 1, preferably 0.35 ≤ d ≤ 0.6.
[0109] In some embodiments, the length of any sub-region in the first direction is 50 to 990 cm. For example, the length of any sub-region in the first direction is, for example, a range of 50 cm, 100 cm, 150 cm, 200 cm, 300 cm, 400 cm, 500 cm, 600 cm, 700 cm, 800 cm, 900 cm, 990 cm, or any combination thereof. When the length of any sub-region in the first direction is within the above range, it can further improve the problem of uneven current density inside the electrode sheet, which is beneficial to improving the cycle life and other performance of the battery. For example, the length of the sub-region closest to the first region in the first direction can be 50 to 990 cm, and the length of the sub-region next closest to the first region in the first direction can be 50 to 990 cm, preferably 50 to 80 cm.
[0110] In some embodiments of the present invention, the electrode sheet further includes a second active layer located on the side of the first active layer opposite to the electrode current collector. Specifically, the first active layer can be directly disposed on the surface of the electrode current collector, meaning there are no other films or spacers between the first active layer and the electrode current collector; it is in direct contact with the electrode current collector. By providing a second active layer in the electrode sheet, it is beneficial to better improve the liquid phase diffusion resistance of the electrode sheet. Simultaneously, it can further mitigate the problem of side reactions between the first active material in the first region of the first active layer and the electrolyte, thus further improving both the cycle life and fast-charging performance of the battery.
[0111] In some embodiments of the present invention, the second active layer includes a second active material, the particle size of which is larger than that of the first sub-active material, and the particle size of the second active material is greater than or equal to that of the first sub-active material in the first region; preferably, the ratio of the particle size of the second active material to the particle size of the first sub-active material in the first region is (1.25-3):1; preferably, the particle size of the second active material is 15-30 μm. By increasing the particle size of the second active material in the electrode sheet, the specific surface area in the second active layer is reduced, thus further improving the problem of side reactions between the active material and the electrolyte in the electrode sheet. Simultaneously, a larger particle size of the active material is more conducive to reducing the areal density and compaction density of the battery, thereby reducing the liquid phase diffusion resistance in the second active layer and improving the cycle life and other performance characteristics of the battery.
[0112] In order to better balance the improvement of liquid phase diffusion resistance of the electrode sheet and the problem of side reactions between the active material and the electrolyte, in some embodiments of the present invention, the thickness of the second active layer is less than the thickness of the first active layer; preferably, the ratio g of the thickness of the second active layer to the thickness of the first active layer is 0.2≤g<1; preferably, the thickness of the second active layer is 15~30μm; preferably, the thickness of the first active layer is 40~80μm.
[0113] Considering the liquid-phase diffusion impedance of the electrode sheet, in some embodiments of the present invention, the compaction density of the active layer is 1.1–2 g / cm³. 2 .
[0114] In some embodiments, the areal density of the active layer is 230–700 g / m³. 2 At this time, the liquid phase diffusion resistance of the second active layer of the electrode sheet is further reduced, which is beneficial to the transport of active metal ions and electrons in the second active layer, and helps to better improve the cycle life and other performance of the battery.
[0115] The active layer in embodiments of the present invention may include only a first active layer, or it may include both a first active layer and a second active layer. Specifically, in some embodiments, when the electrode sheet includes only a first active layer, the areal density and compaction density of the active layer are the same as those of the first active layer; in some embodiments, when the electrode sheet includes both a first active layer and a second active layer, the areal density and compaction density of the active layer are the same as those of the first and second active layers.
[0116] In this embodiment of the invention, the process of testing the areal density of the electrode coating may include: taking an electrode sheet sample, testing the total mass m1 of the electrode sheet sample and the surface area S of one side of the electrode sheet sample in the thickness direction; then scraping off the electrode coating on the electrode sheet sample, testing the mass m2 of the obtained electrode current collector, and then the areal density of the electrode coating = (m1-m2) / S.
[0117] In this embodiment of the invention, the compaction density of the electrode coating = the areal density of the electrode coating / the total thickness of the electrode coating. The testing process for the areal density of the electrode coating is as described above. The testing process for the total thickness of the electrode coating may include: taking an electrode sheet sample and testing the total thickness T1 of the electrode sheet sample (T1 = total thickness of the electrode coating + thickness of the electrode current collector; when both the front and back surfaces of the electrode current collector are respectively provided with electrode coatings, the total thickness of the electrode coating = the thickness of the electrode coating on one side of the electrode current collector + the thickness of the electrode coating on the other side of the electrode current collector); then scraping off the electrode coating on the electrode sheet sample and testing the thickness T2 of the obtained electrode current collector. Then the total thickness of the electrode coating = T1 - T2.
[0118] In practice, a micrometer can be used to measure the average thickness T1 of the electrode sheet and the average thickness T2 of the electrode current collector.
[0119] In practice, the battery can be disassembled to obtain electrode sheets, and then the areal density and compaction density of the electrode sheets can be tested.
[0120] In some embodiments of the present invention, the length of the first region in the first direction is a proportion i of the length of the first active layer in the first direction that is 0.01 ≤ i < 1. The first direction is parallel to the direction from the first region to the second region. When the length of the first region in the first direction is within the above-mentioned range as a proportion of the length of the first active layer in the first direction, it can further improve the problem of increased battery internal resistance caused by uneven current density, which is beneficial to further improving the battery's cycle life and other performance characteristics.
[0121] In some embodiments, the length of the first region in the first direction is 1 to 950 cm. For example, the length of the first region in the first direction is, for example, a range of 1 cm, 10 cm, 50 cm, 100 cm, 200 cm, 300 cm, 400 cm, 500 cm, 600 cm, 700 cm, 800 cm, 900 cm, 950 cm, or any combination thereof. The fact that the length in the first direction of the embodiments of the present invention is within the above-mentioned range can better improve the current density uniformity and other properties of the electrode sheet during battery cycling, thereby improving the cycle life and other performance characteristics of the battery.
[0122] In some embodiments of the present invention, there are second regions on both sides of the first region, which is more conducive to improving the current density uniformity and other properties of the electrode sheet during battery cycling, and to improving the cycle life and other performance of the battery.
[0123] In some embodiments, the first region and the second region are distributed along the length direction of the electrode sheet, that is, they are distributed parallel to the length direction of the electrode sheet (which is also the length direction of the electrode current collector) along the direction from the first region to the second region.
[0124] In some embodiments of the present invention, the electrode sheet further includes a tab connected to the electrode current collector, and the second region is located between the first region and the tab.
[0125] In this embodiment of the invention, the electrode sheet is either a negative electrode sheet or a positive electrode sheet.
[0126] Specifically, in some embodiments, the positive electrode tab 31 can be provided on the positive electrode sheet 3 in a manner conventional in the art. For example, the positive electrode tab 31 can be welded to the positive current collector or extended outward from the positive current collector, without any particular limitation.
[0127] In detail, such as Figure 3 As shown, the negative electrode tab 41 can be provided on the negative electrode sheet 4 in a conventional manner in the art. For example, the negative electrode tab 41 can be welded to the negative electrode current collector, or it can be formed by extending outward from the negative electrode current collector. There are no particular limitations on this.
[0128] In some embodiments, the electrode sheet can be a negative electrode sheet, and correspondingly, the electrode current collector is a negative electrode current collector, the electrode coating is a negative electrode coating (a first active layer and a second active layer or a first active layer), and the first active material and the second active material are negative electrode active materials, which may include graphite, such as artificial graphite and / or natural graphite, and the electrode coating may specifically include primary graphite particles and / or secondary graphite particles.
[0129] The embodiments of the present invention may employ conventional negative electrode current collectors in the art, for example, negative electrode current collectors include copper foil.
[0130] In detail, during battery cycling, the internal resistance of the negative electrode current collector leads to uneven current density within the negative electrode. During charging, active metal ions easily precipitate on the surface of the negative electrode, increasing the battery's internal resistance and thus affecting its cycle life. This invention addresses this issue by configuring the negative electrode with a structure of rationally ordered stacked active particles. This allows the battery to perform better under high areal density and compaction conditions, improving the uneven current density distribution within the negative electrode and thereby enhancing the battery's cycle life.
[0131] In other embodiments, the electrode sheet is a positive electrode sheet, and correspondingly, the electrode current collector is a positive electrode current collector, the electrode coating is a positive electrode coating (a first active layer and a second active layer or a first active layer), and the first active material and the second active material are positive electrode active materials, which may include positive electrode ternary materials and / or lithium iron phosphate, wherein the positive electrode ternary materials include, for example, nickel-cobalt-manganese ternary materials and / or nickel-cobalt-aluminum ternary materials.
[0132] The embodiments of the present invention may employ conventional positive current collectors in the art, for example, positive current collectors may include aluminum foil.
[0133] This invention also provides a method for preparing the above-mentioned electrode sheet, comprising the following steps:
[0134] A first electrode paste is coated on at least one side of an electrode current collector to form a first active layer, thereby obtaining an electrode sheet. The first electrode paste includes a first paste for forming a first region and a second paste for forming a second region. The first paste is coated on the electrode current collector at a position corresponding to the first region to form a first region of the first active layer, and the second paste is coated on the electrode current collector at a position corresponding to the second region to form a second region of the first active layer.
[0135] In detail, in some embodiments of the present invention, the first electrode slurry includes a first active material, as described above. The first active material includes a first sub-active material and a second sub-active material. The particle size of the second sub-active material is larger than that of the first sub-active material. In the above preparation process, the first sub-active material and the second sub-active material can be mixed to form the first electrode slurry, or the first sub-active material can be first formed into a first sub-active material slurry, the second sub-active material can be formed into a second sub-active material slurry, and then the first sub-active material slurry and the second sub-active material slurry can be combined to form the first electrode slurry.
[0136] In the above preparation process, the embodiment of the present invention controls the n value of the first slurry to be less than the n value of the second slurry.
[0137] By using the above method, the embodiments of the present invention can prepare electrode sheets with more uniform current density distribution, which is beneficial to improving the cycle life and other performance of the battery.
[0138] In this embodiment of the invention, an electrode coating (first active layer) can be provided on one side surface of the electrode current collector, or an electrode coating (first active layer) can be provided on both sides of the electrode current collector. When an electrode coating is provided on both sides of the electrode current collector, the electrode coating on one side surface can be an electrode coating designed with different particle sizes in the aforementioned regions (i.e., the n value of the electrode active material (first active material) in the first region is less than the n value of the first active material in the second region), or the electrode coatings on both sides of the electrode current collector can be electrode coatings designed with different n values in the aforementioned regions.
[0139] Generally, the aforementioned electrode coating also includes a conductive agent and a binder. Based on the total mass of the electrode coating, the mass fraction of the electrode active material (first active material) (i.e., the ratio of the mass of the electrode active material to the total mass of the electrode coating) can be 70% to 99%, for example, 70%, 75%, 80%, 85%, 90%, 93%, 95%, 97%, 99%, or any combination thereof. The mass fraction of the conductive agent can be 0.5% to 15%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 8%, 10%, 13%, 15%, or any combination thereof. The mass fraction of the binder can be 0.5% to 15%, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 8%, 10%, 13%, 15%, or any combination thereof.
[0140] In this embodiment of the invention, the conductive agent in the electrode coating 1 can be a conventional conductive material in the art, such as one or more of carbon black, carbon nanotubes (CNT), acetylene black, graphene, Ketjen black, and carbon fiber.
[0141] In this embodiment of the invention, the binder in the electrode coating can be a conventional adhesive material in the art. For example, when the electrode sheet is a negative electrode sheet, the binder may include one or more of carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate. When the electrode sheet is a positive electrode sheet, the binder may include one or more of polyvinylidene fluoride (PVDF), polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinylpyrrolidone, and polyurethane.
[0142] In this embodiment of the invention, when electrode coatings are formed on both the front and back surfaces of the electrode current collector, a slurry containing electrode active material can be first coated on one side surface of the electrode current collector, and then induced and dried by a magnetic field. Then, a slurry containing electrode active material can be coated on the other side surface of the electrode current collector, and then induced and dried by a magnetic field. Finally, the electrode sheet is rolled to obtain the electrode sheet.
[0143] In this embodiment of the invention, drying (baking) and rolling can also be conventional operations in the art, and there are no particular limitations on them.
[0144] In some embodiments of the present invention, a second electrode slurry including a second active material may be coated on the side of the first active layer away from the electrode current collector to form a second active layer.
[0145] In this embodiment of the invention, a slurry containing electrode active materials (in the first region) can be prepared using conventional methods in the art. For example, when the electrode sheet is a negative electrode sheet, the components used to form the negative electrode coating, such as the negative electrode active material, conductive agent, and binder, can be dispersed in a first solvent, which may include, for example, deionized water and / or N-methylpyrrolidone (NMP), to prepare a negative electrode slurry (i.e., a slurry containing electrode active materials). This slurry is then coated onto the surface of the negative electrode current collector, and after drying, rolling, and other processes, a negative electrode sheet is obtained. When the electrode sheet is a positive electrode sheet, the components used to form the positive electrode coating, such as the positive electrode active material, conductive agent, and binder, can be dispersed in a second solvent, which may include, for example, N-methylpyrrolidone (NMP), to prepare a positive electrode slurry (i.e., a slurry containing electrode active materials). This slurry is then coated onto the surface of the positive electrode current collector, and after drying, rolling, and other processes, a positive electrode sheet is obtained.
[0146] In practice, a slurry containing electrode active materials can be prepared at a temperature of 20–45°C; and conventional coating equipment in the field, such as continuous coating equipment, can be used to coat the slurry containing electrode active materials onto the surface of the electrode current collector.
[0147] This invention also provides a battery comprising the above-described electrode sheet or an electrode sheet prepared according to the above-described electrode sheet preparation method. This battery has advantages corresponding to the above-described electrode sheet, which will not be elaborated further.
[0148] The battery in this embodiment of the invention can be a lithium-ion battery (such as a lithium-ion power battery), a solar cell, or other novel energy storage battery.
[0149] Generally, a battery consists of an electrolyte, a battery cell, and a package containing the battery cell. The electrolyte is injected into the battery cell within the package, such as... Figure 3 As shown, the battery cell includes a positive electrode 3, a negative electrode 4, and a separator 5 located between the positive electrode 3 and the negative electrode 4.
[0150] In this embodiment of the invention, at least one of the positive electrode 3 and the negative electrode 4 is an electrode sheet designed with different n values in the aforementioned regions. That is, the positive electrode 3 can be an electrode sheet designed with different n values in the aforementioned regions (i.e., the n value of the first active material in the first region is less than the n value of the first active material in the second region), or the negative electrode 4 can be an electrode sheet designed with different n values in the aforementioned regions (i.e., the n value of the first active material in the first region of the negative electrode coating is less than the n value of the first active material in the second region), or both the positive electrode 3 and the negative electrode 4 are electrode sheets designed with different n values in the aforementioned regions.
[0151] Specifically, the battery cell can be a laminated battery cell, that is, the battery cell is composed of positive electrode 3, separator 5 and negative electrode 4 stacked alternately.
[0152] The electrolyte in this embodiment of the invention can be a conventional electrolyte in the art. For example, the electrolyte is a non-aqueous electrolyte, which may specifically include an organic solvent and an electrolyte salt. The organic solvent may include, for example, ethylene carbonate and / or diethyl carbonate. When the battery is a sodium-ion battery, the electrolyte salt may include a lithium salt, such as lithium hexafluorophosphate (LiPF6), but is not limited thereto.
[0153] In this embodiment of the invention, the separator 5 is used to separate the positive electrode 3 and the negative electrode 4 to prevent the positive electrode 3 and the negative electrode 4 from short-circuiting due to contact. Conventional separators in the art can be used in this embodiment of the invention, and there are no special limitations on this.
[0154] In this embodiment of the invention, the battery cell can be packaged using conventional encapsulation (shell) materials in the art, and the battery can be a conventional battery type and structure in the art. For example, the battery can be a blade battery, but it is not limited to this.
[0155] The embodiments of the present invention can assemble components such as the positive electrode 3, the separator 5, and the negative electrode 4 into a battery using conventional methods in the art, and there are no particular limitations on this.
[0156] This invention also provides an electrical device including the battery described above. This electrical device has advantages corresponding to the electrode plates described above, which will not be elaborated further.
[0157] The electrical equipment in the embodiments of the present invention can be conventional electrical equipment in the art, such as power equipment (e.g., electric vehicles, electric cars), electronic equipment (e.g., mobile phones, tablets, laptops, digital cameras, etc.), wearable devices (e.g., watches, bracelets, VR glasses, etc.), energy storage power stations, etc., and there are no particular limitations.
[0158] The technical solution of the present invention will be further described below with reference to specific embodiments.
[0159] Example 1
[0160] The negative electrode sheet in this embodiment is prepared by the following method:
[0161] Graphite (both the first and second active materials have a particle size of 10 μm), carbon black, CMC, and SBR are mixed at 25°C in a mass ratio of 100:1:1.6:3.3 to obtain a first slurry for forming the first region. Graphite (the first active material has a particle size of 11 μm), carbon black, CMC, and SBR are mixed in a mass ratio of 100:1:1.6:3.3 to obtain a second slurry for forming the sub-region closest to the first region. Graphite (the first active material has a particle size of 14 μm), carbon black, CMC, and SBR are mixed in a mass ratio of 100:1:1.6:3.3 to obtain a slurry for forming the sub-region closest to the first region. The second slurry for the sub-regions is formed by coating the first slurry onto the negative electrode current collector (copper foil) at the position corresponding to the first region using a continuous coating equipment to form the first region of the first active layer. The second slurry is then coated onto the negative electrode current collector (copper foil) at the position corresponding to the second region (the sub-region closest to the first region and the sub-region second closest to the first region) to form the second region of the first active layer. Graphite (particle size of 10μm), carbon black, CMC, and SBR are mixed in a mass ratio of 100:1:1.6:3.3 to obtain the second electrode slurry for forming the second active layer. The second electrode slurry is then coated onto the side of the first active layer away from the electrode current collector using a continuous coating equipment to form the second active layer.
[0162] The first region of the aforementioned negative electrode sheet has a length of 10 cm in the first direction; the sub-region closest to the first region has a length of 50 cm in the first direction; the sub-region next closest to the first region has a length of 80 cm in the first direction; the thickness of the first active layer is 63 μm, and the thickness of the second active layer is 22 μm; the compaction density of the second active layer is 1.61 g / cm³, and the areal density of the second active layer is 230 g / cm³. 2 .
[0163] The n-values of the first region and the second region of the negative electrode sheet prepared in this embodiment, the particle size of the first sub-active material in the first region, the n-value of the sub-region closest to the first region, the particle size of the first sub-active material in the sub-region closest to the first region, and the particle size of the first sub-active material in the sub-region second closest to the first region are shown in Table 1. The particle size of the second active material, the thickness of the second active layer, the length of the first region in the first direction, the length of the sub-region closest to the first region in the first direction, the length of the sub-region second closest to the first region in the first direction, the areal density of the second active layer, and the compaction density of the second active layer are shown in Table 2.
[0164] The differences between Examples 2-23, Comparative Example 2 and Example 1 are as follows: the n-value of the first region, the n-value of the second region, the particle size of the first sub-active material in the first region, the n-value of the sub-region closest to the first region, the particle size of the first sub-active material in the sub-region closest to the first region, the particle size of the first sub-active material in the sub-region second closest to the first region, the particle size of the second active material, the thickness of the second active layer, the length of the first region in the first direction, the length of the sub-region closest to the first region in the first direction, the length of the sub-region second closest to the first region in the first direction, the areal density of the active layer, and the compaction density of the active layer. In addition, Example 4 does not have a second active layer, and Comparative Example 1 does not have a second region (that is, the entire negative electrode sheet only has the first region). See Tables 1 and 2 for details.
[0165] Table 1
[0166]
[0167]
[0168] Table 2
[0169]
[0170]
[0171] Test case
[0172] The negative electrode sheets from the above embodiments and comparative examples were assembled into batteries, and then EIS liquid phase diffusion test, porosity test, 50% SOC DC internal resistance test, and long cycle test were performed.
[0173] The battery assembly process is as follows: Lithium iron phosphate, CNT, carbon black, and PVDF are mixed in a mass ratio of 100:0.3:0.5:2.5, and NMP is added. The mixture is stirred evenly to prepare a positive electrode slurry with the corresponding dimensions and areal density of 500 g / m³. 2 The positive electrode lithium iron phosphate electrode is matched with the negative electrode; then 1 mol of lithium salt LiPF6 is dissolved in 1 L of organic solvent (the volume ratio of ethylene carbonate and diethyl carbonate is 1:1) to obtain the electrolyte; the prepared positive electrode, separator and negative electrode are alternately stacked and injected into the electrolyte to assemble a battery with a designed capacity of 120 Ah.
[0174] EIS Liquid Phase Diffusion Testing: EIS liquid phase diffusion testing was performed using an electrochemical workstation, INTERFACE 1010E. Electrochemical impedance spectroscopy (EIS) involves applying small-amplitude alternating current potential waves of different frequencies to an electrochemical system and measuring the change in the system's impedance as a function of the sinusoidal wave frequency. Symmetrical cells, which simplify electrochemical systems composed of two identical working electrodes, can be used to quantify the tortuosity of electrodes with different electrode compositions and porosities. Using Examples 1-4 and Comparative Examples 1-2 as examples, the test results are shown in Table 3, where R1 is the liquid phase diffusion resistance of the first region, R2 is the liquid phase diffusion resistance of the sub-region closest to the first region, and R3 is the liquid phase diffusion resistance of the sub-region second closest to the first region.
[0175] Porosity testing: With relatively low interfacial tension, external pressure is applied to metallic mercury. The greater the external pressure, the smaller the pore radius that mercury can enter. For a cylindrical pore model, the pore size that mercury can enter conforms to the Washburn equation. By controlling different pressures, the volume of mercury in the pore can be measured, thus obtaining the cumulative distribution curve or differential curve of the pore size corresponding to different pressures. Taking Examples 1-4 and Comparative Examples 1-2 as examples, the test results are shown in Table 3, where ε1 is the porosity of the first region, ε2 is the porosity of the sub-region closest to the first region, and ε3 is the porosity of the sub-region second closest to the first region.
[0176] The formula for calculating tortuosity is:
[0177]
[0178] Where K0 refers to the electrolyte conductivity, which is 0.883 μS / m; ε refers to the theoretical porosity (measured using the mercury porosimetry method), obtained through the aforementioned porosity test; and S is the electrode sheet coating area (active layer area), which is 0.004662 m². 2 ;R iτ1 represents the liquid-phase diffusion resistance of ions (active metal ions) per unit area within the electrode sheet (measured using the aforementioned electrochemical workstation); d0 represents the electrode sheet thickness, which is 0.000144 μm. Taking Examples 1-4 and Comparative Examples 1-2 as examples, the test results are shown in Table 3, where τ1 represents the tortuosity of the first region, τ2 represents the tortuosity of the sub-region closest to the first region, and τ3 represents the tortuosity of the sub-region second closest to the first region.
[0179] 50% SOC DC internal resistance test: The state of charge of the above batteries was adjusted to 50% SOC (V1) at 25℃, and then charged at 1.5C for 30s (I, V2) respectively. The voltage drop of each battery was recorded, and the DC resistance DCIR was calculated as follows: DCIR = (V2 - V1) / I. The results are shown in Table 4.
[0180] Battery long-cycle performance test: The battery's long-cycle performance was measured at 25℃ using an INTERFACE 1010E electrochemical workstation. Specifically, the battery was discharged at 0.5C constant current to 2.0V, charged at 0.5C constant current to 3.8V, charged at 0.2C constant current to 3.8V, and cycled until the state of charge (SOC) reached 80% of its original value. The number of cycles was recorded. The results are shown in Table 4.
[0181] Table 3
[0182]
[0183]
[0184] Table 4
[0185]
[0186]
[0187] As shown in the table, compared to Comparative Examples 1-2, the battery electrode design of Examples 1-21 of the present invention, which involves orderly stacking of active particles (the n-value of the first region is less than that of the second region), exhibits significantly lower DC internal resistance and better cycle life than unused batteries. When using a non-forward arrangement and without a second active layer, the cycle performance is greatly reduced. Compared to Example 4, the embodiments of the present invention further improve the cycle life of the battery by using a second active layer.
[0188] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. An electrode sheet, characterized in that, include Electrode current collector; Active layer; The active layer includes a first active layer located on at least one side of the electrode current collector, the first active layer including a first active material, the first active material including a first sub-active material and a second sub-active material; The first active layer includes a first region and a second region located on at least one side of the first region, wherein the second region is located between the first region and the outer edge of the electrode sheet; The n value of the first region is less than the n value of the second region; The value of n is the ratio of the particle size of the second sub-active material to the particle size of the first sub-active material, and the value of n is ≥1.
2. The electrode sheet according to claim 1, characterized in that, The value of n in the first region is between 1 and 1.1; And / or, the particle size of the first sub-active material in the first region is smaller than the particle size of the first sub-active material in the second region; And / or, the particle size of the first sub-active material in the first region is 5 to 15 μm, preferably 10 to 12 μm; And / or, the particle size of the second sub-active material in the first region is 5 to 17 μm, preferably 10 to 14 μm.
3. The electrode sheet according to claim 1 or 2, characterized in that, The second region includes at least two sub-regions distributed along a first direction, which is parallel to the direction from the first region to the second region; in every two adjacent sub-regions, the n value of the sub-region closer to the first region is less than the n value of the sub-region farther from the first region.
4. The electrode sheet according to claim 3, characterized in that, The ratio a of the n value of the sub-region closest to the first region to the n value of the first region is 1 < a < 1.35, preferably a of 1.12 ≤ a ≤ 1.31; And / or, the n value of the sub-region closest to the first region is 1 < n < 1.35, preferably the n value of the sub-region closest to the first region is 1.12 ≤ n ≤ 1.31; And / or, the n value of the sub-region next to the first region is 1.35≤n≤4, preferably the n value of the sub-region next to the first region is 1.8≤n≤2.2; And / or, in any two adjacent sub-regions, the ratio b of the n value of the sub-region farther from the first region to the n value of the sub-region closer to the first region is 1 < b < 4, preferably b of 1.36 ≤ b ≤ 2; And / or, the particle size of the first sub-active material in the first region is smaller than the particle size of the first sub-active material in the sub-region closest to the first region, preferably the ratio of the particle size of the first sub-active material in the sub-region closest to the first region to the particle size of the first sub-active material in the first region is (1~1.5):1; preferably the ratio of the particle size of the first sub-active material in the sub-region closest to the first region to the particle size of the first sub-active material in the first region is (1.1~1.2):1; And / or, the particle size of the first sub-active material in the sub-region closest to the first region is 8 to 30 μm; And / or, the particle size of the first sub-active material in the sub-region closest to the first region is 12-40 μm; And / or, in any two adjacent sub-regions, the particle size of the first sub-active material in the sub-region closer to the first region is smaller than the particle size of the first sub-active material in the sub-region farther from the first region. Preferably, the ratio of the particle size of the first sub-active material in the sub-region farther from the first region to the particle size of the first sub-active material in the sub-region closer to the first region is (1.15 to 5):1; preferably, the ratio of the particle size of the first sub-active material in the sub-region farther from the first region to the particle size of the first sub-active material in the sub-region closer to the first region is (1.2 to 1.8). And / or, in any two adjacent sub-regions, the length of the sub-region closer to the first region in the first direction is less than the length of the sub-region farther from the first region in the first direction, preferably the ratio of the length of the sub-region closer to the first region in the first direction to the length of the sub-region farther from the first region in the first direction is (0.6~1):1; And / or, the ratio d of the length of any of the sub-regions in the first direction to the length of the first active layer in the first direction is 0.05 ≤ d < 1, preferably 0.35 ≤ d ≤ 0.6; And / or, the length of any of the sub-regions in the first direction is 50 to 990 cm, preferably 50 to 80 cm.
5. The electrode sheet according to any one of claims 1-4, characterized in that, It also includes a second active layer located on the side of the first active layer opposite to the electrode current collector.
6. The electrode sheet according to claim 5, characterized in that, The second active layer includes a second active material, the particle size of which is greater than or equal to the particle size of the first sub-active material in the first region; Preferably, the particle size ratio of the second active material to the particle size of the first sub-active material in the first region is (1.25~3):1; Preferably, the particle size of the second active material is 15–30 μm.
7. The electrode sheet according to claim 5 or 6, characterized in that, The thickness of the second active layer is less than the thickness of the first active layer; Preferably, the ratio g of the thickness of the second active layer to the thickness of the first active layer is 0.2 ≤ g < 1; Preferably, the thickness of the second active layer is 15–30 μm; Preferably, the thickness of the first active layer is 40–80 μm.
8. The electrode sheet according to claim 5 or 6, characterized in that, The compaction density of the active layer is 1.1–2 g / cm³. 2 ; And / or, the areal density of the active layer is 230–700 g / m³. 2 .
9. The electrode sheet according to any one of claims 1-8, characterized in that, The length of the first region in the first direction is a proportion i of the length of the first active layer in the first direction, where i is 0.01 ≤ i < 1; And / or, the length of the first region in the first direction is 1 to 950 cm; Wherein, the first direction is parallel to the direction along the first region to the second region.
10. The electrode sheet according to any one of claims 1-8, characterized in that, The second region exists on both sides of the first region; And / or, the first region and the second region are distributed along the length of the electrode sheet.
11. The electrode sheet according to any one of claims 1-10, characterized in that, The electrode sheet also includes a tab connected to the electrode current collector, and the second region is located between the first region and the tab.
12. The electrode sheet according to any one of claims 1-10, characterized in that, The electrode sheet can be a negative electrode sheet or a positive electrode sheet.
13. A method for preparing an electrode sheet according to any one of claims 1-12, characterized in that, Includes the following steps: The first electrode paste is coated on at least one side of the electrode current collector to form the first active layer, thereby obtaining the electrode sheet; The first electrode paste includes a first paste for forming the first region and a second paste for forming the second region. The first paste is applied to the electrode current collector at a position corresponding to the first region to form the first region of the first active layer, and the second paste is applied to the electrode current collector at a position corresponding to the second region to form the second region of the first active layer.
14. A battery, characterized in that, This includes the electrode sheet as described in any one of claims 1-12 or the electrode sheet prepared according to the method described in claim 13.
15. An electrical appliance, characterized in that, Includes the battery as described in claim 14.